IMPLEMENTING A SPIRAL CURRICULUM IN LANGUAGE EDUCATION: THEORY, PRACTICE AND CASE ILLUSTRATIONS - Nasiba Jakbarova (Journal Park Publishing, 2025)
This paper explores the theoretical basis of the spiral curriculum, its adaptation for English as a Foreign Language (EFL) context, and its implications for language skill development. A quasi-experimental study in an Uzbek secondary school demonstrates how cyclic reinforcement of linguistic structures enhances vocabulary retention, grammatical accuracy, and communicative competence. The results affirm that spiral sequencing supports cumulative learning and fosters learner autonomy. The discussion highlights pedagogical implications, challenges in implementation, and recommendations for language teachers and curriculum designers.